Improving the Students’ Listening Comprehension through Drill Technique - Wirathama Hazera Putra (TEKNOSASTIK, 2018)
This research was aimed at: 1) analyzing the improvement of the students’ listening comprehension through drill technique, 2) finding out the problems the students face in learning micro skills of listening comprehension through drill technique. The data were obtained from the pre-test and post-test to analyze the improvement of the students’ listening comprehension through drill technique, and also from the observation and interview to find out the problems the students face in learning micro skills of listening comprehension through drill technique. The result showed that the students’ mean score of the pre-test was 52.2 and their mean score of the post-test after being taught through drill technique was 78.5, in which their gain score was 26.3. Specifically, drill technique improved the students’ listening comprehension in all aspects of micro skill types of listening comprehension, such as recognition intonation pattern, recognition sentence pattern, recognition discourse marker, and getting the referential info. Moreover, drill technique mostly improved the students’ listening comprehension in recognizing intonation pattern, in which their ability in that aspect was 38 % improved significantly. Besides that, in line with what had been observed during the treatment, the problems the students faced in learning micro skills of listening comprehension through drill technique could be divided into: a) Problems from the listener, in example: understanding the difficult words/phrases, recognizing phonetic symbols and intonation pattern, distinguishing sentence pattern and discourse marker, and unable to keep up with the native speaker’s speed; b) Problem from listening materials, in example some dialogues were long. However, after practicing the dialogues more frequently through drill technique, the students gradually started to comprehend the materials and were able to overcome those problems. Based on the results above, it could be concluded that: 1) drill technique could improve the students’ listening comprehension better and significantly, especially in recognizing intonation pattern, 2) drill technique could overcome the problems the students faced during the treatment of teaching listening through drill technique.Key Words: Drill technique, listening comprehension